Evaluating photoneutron dose equivalents for lung cancer using PMMA phantoms undergoing 15 MV IMRT. - Xu, Hai-Bing; Dong, An-Ding; Liu, Mu-Tai; Tseng, Hsien-Chun; Chen, Chien-Yi; Tsai, Sung-Yi (Technology & Health Care)
Background: According to statistics of the Ministry of Health and Welfare in 2017, the second leading cause of death in Taiwan was lung cancer.Objective: Routine treatment planning does not consider photoneutron dose equivalent (PNDE) of patient induced secondary radiation resulting from primary exposure of lung cancer. However, such treatment is potentially important for improving estimates of health risks.Methods: This study used 10, 30, 50, 70, and 90 kg of polymethylmethacrylate (PMMA) phantoms as patient to measure PNDE varying anatomical area during lung cancer of intensity modulated radiotherapy (IMRT) treatment. Paired thermoluminescent dosimeters (TLD-600 and 700) were calibrated using university reactor neutrons. TLDs were inserted into phantom which was closely corresponded of the represented tissues or organs.Results: Neutron doses (ND) of organ or tissue (N⁢DT) were determined in these phantoms using paired TLDs approach. The risks of incurring fatal secondary malignancies, maximum statistical and total errors were estimated. Evaluated PNDE ranged from 0.80 ± 0.12 to 0.56 ± 0.08 mSv/Gy for these phantoms.Conclusion: The estimated N⁢DT decreased with increasing distance that is from the central axis. Evaluated PNDE and N⁢D푠푘푖푛 for these phantoms were discussed. This investigation also identified secondary risks associated with PNDE relating to radiation protection.